Analysis of the Determinants of Diabetes Mellitus in Indonesia: A Case Study of the 2014 Indonesian Family Life Survey - Kamilah, Fariza Zahra; Habibie, Farhan; Rahma, Gina Ridhia; Sofyan, Mohammad Naufal Faisal; Isnaini, Nurma Sari; Nadhilah, Nurul Dita; Sihaloho, Estro Dariatno (Universitas Ahmad Dahlan, 2021)
Background: Diabetes mellitus (DM) is a disease of excessive blood sugar levels. Data from the Indonesian Ministry of Health shows that several DM survivors have had DM for over 15 years reached 19.98 million or 10.9% of the Indonesian population in 2019 with population data according to the Central Bureau of Statistics Republic of Indonesia. This research aimed to determine factors affecting DM in Indonesia. Method: This was a study with a cross-sectional design. The data used in this study came from the fifth wave of the Indonesian Family Life Survey (IFLS). A total of 34,257 individuals aged 14 or over as samples. The dependent variable was diabetes mellitus, while independent variables were obesity, hypertension, quality of sleep, and socio-economic factors. The data measurement was performed by logistic regression. Â Results: The research found that obesity, hypertension, and poor sleep quality will increase the risk of DM and also the risk will increase due to socio-economic factors like age, education, household income, urban, and marital status. Conclusion: This study found that the driving force for DM in Indonesia is obesity, hypertension, and sleep quality.